Potential impacts of land use changes on water resources in a tropical headwater catchment - Martins, Magda Stella de Melo [UNESP] (2021)
The main objective of this study was to investigate the relationships between land use and future scenarios of land changes on water runoff and groundwater storage in an Environmental Protection Area (EPAs) watershed. The methodology was based on the application of the Soil and Water Assessment Tool (SWAT) hydrological modelling to investigate flow simulations in current land use and in two future scenarios (forest and pasture). The performance of goodness-of-fit indicators in the calibration (NSE = 0.82, R2 = 0.85, PBIAS = 11.9% and RSR = 0.42) and validation (NSE = 0.70, R2 = 0.72, PBIAS = −4% and RSR = 0.55) was classified as good and very good, respectively. The model accurately reproduced the inter-annual distribution of rainfall. The spatial distribution of average annual surface flow, lateral flow, and groundwater flow were different between sub-basins. The future scenario on land use change to forest (FRSE) and pasture (PAST) differed during the year, with greater changes on rainy and dry seasons. FRSE increase of 64.5% in area led to decreased surface runoff, total runoff, and soil water; and increased lateral flow, groundwater, and evapotranspiration. The effect of the natural vegetation cover on soil moisture content is still unclear. The hydrological model indicated the main areas of optimal spatial water flow. Considering economic values, those areas should encourage the development of government policies based on incentive platforms that can improve environmental soil and water sustainability by establishing payment for environmental services (PES).